Evaluation of the application value of ultrasound in the diagnosis of community-acquired pneumonia in children: a preliminary study based on large-scale outpatient cases - Qin, Tingting; Huang, Zengpo; Lan, Qiuhui; Nie, Yijun; Luo, Guofei; Cheng, Lixue; Li, Linglin; Tang, Zhixuan; Ma, Zhao (Frontiers in Pediatrics, 2025)
ObjectiveTo evaluate the diagnostic value of lung ultrasound (LUS) for childhood community-acquired pneumonia (CAP).MethodsA case-control study was conducted among pediatric outpatients with suspected CAP who underwent LUS examination. Baseline data such as clinical manifestations were collected. Diagnostic performance was assessed using Pearson Chi-square tests, with CT scans as the gold standard. Specificity, sensitivity, positive predictive value (PPV), and negative predictive value (NPV) of LUS were analyzed.ResultsThe study included 246 patients who underwent both LUS and CT (observation group) and 111 controls who received concurrent chest x-ray and CT within one week. LUS demonstrated significantly higher sensitivity (91.30% vs. 75.00%, P < 0.001) than chest x-ray group, while specificity, PPV, and NPV showed no statistically significant (P > 0.05).ConclusionLUS exhibits high concordance with CT in pediatric CAP diagnosis, demonstrating excellent screening and diagnostic value for childhood CAP.